FAKTOR Ã¢â¬â FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Haritsman, Egi; Usman, Bahtiar (Manajemen Bisnis Kompetensi, 2017)
ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ AbstractThis study discusses the influence of capital adequcy, credit risk, liquidity, economic growth, inflation, and domestic credit to pivate sector on return on average assets and net interest margin at conventional banks listed on the Indonesia Stock Exchange (IDX). The samples are 30 conventional banks listed on the Indonesia Stock Exchange (IDX) for 5 years from 2010-2014. The research method used in this research is multiple linear regression. The results show that there is a positive influence between the capital adequacy on return on average assets, there is a positive influence between capital adequacy and liquidity on net interest margin, and there is a negative effect of credit risk on return on average assets. These results indicate there is no influence between economic growth, inflation, and domestic credit to pivate sector of the return on average assets and net interest margin. To improve the profitability of banks, capital adequacy needs to be increased so did the liquidity of banks in providing credit, but it should be noted that the high level of credit risk may reduce the profitability of banks.Keywords:ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ Capital Adequacy, Credit Risk, Domestic Credit to Private Sector, Economic Growth, Inflation, Liquidity, Net Interest Margin (NIM), Return on Average Asset (ROAA).